The Representation of Profit from a Conventional Economic Perspective in Aceh - Mona Afliana; Tri Pertiwi; Putri Rahmah Nur Hakim (CV. ITTC INDONESIA, 2026)
This study examines the complex dynamics of religious identity representation among hijab-wearing Muslim female TikTokers in Aceh, focusing on how Islamic symbols, personal narratives, and platform algorithms shape public perceptions of piety in digital spaces. The research aims to identify the strategies used by creators to negotiate between local Islamic norms and the expressive culture of TikTok, as well as to analyze how audiences interpret these representations. Using a qualitative descriptive method, the study collected data through in-depth interviews with content creators, observation of TikTok videos, and documentation of public responses. The findings reveal three dominant patterns: the aestheticization of Islamic identity, the commodification of piety, and the negotiation of moral boundaries within digital performance. These results contribute to broader discussions on digital religion and Muslim women’s agency in online media, while also highlighting the impact of algorithm-driven visibility.